Penerapan Sub Pokok Fungsi pada Matematika Ekonomi terhadap Fungsi Permintaan dan Fungsi Penawaran - Puspaningrum, Cici (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This article discusses the results of research on the application of sub-functions in economic mathematics to demand and supply functions. Function material is often used by experts in solving economic problems. The purpose of this study was to determine student activity during learning sub-functions in economic mathematics to demand and supply functions, to determine student responses when learning functions in economic mathematics to demand and supply functions. The research method used was quasi-experimental, with a one-shot case study research design. The population of this study were all students of the Accounting study program and the sample was students of the Accounting study program in the first semester of STIE Bina Karya Tebing Tinggi. The statistics used in this study were descriptive statistics with the data analyzed being qualitative data. The research instruments used were observations of student activities and observations of lecturers' activities in teaching, interviews, and Likert-scale questionnaires. Based on the analysis of student observation sheets, student activity during learning sub-functions in economic mathematics to demand and supply functions increased. Based on the analysis of the questionnaire, students responded positively to the learning of sub-topics of functions in economic mathematics regarding demand functions and supply functions.